2011
DOI: 10.1007/s10534-011-9459-9
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization and ultrastructural alterations induced by chromium in aquatic macrophytes

Abstract: The aim of the present study was to identify the sites of accumulation of Cr in the species of macrophytes that are abundant in the Cachoeira river, namely, Alternanthera philoxeroides, Borreria scabiosoides, Polygonum ferrugineum and Eichhornia crassipes. Plants were grown in nutritive solution supplemented with 0.25 and 50 mg l(-1) of CrCl(3)·6H(2)O. Samples of plant tissues were digested with HNO(3)/HCl in a closed-vessel microwave system and the concentrations of Cr determined using inductively-coupled pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…crassipes accumulated higher Cr concentrations in roots than in the aerial parts of the plant (Figs. 1 and 2), in agreement with many authors (Ingole and Bhole 2003;Maine, et al 2004;Paiva et al 2009;Hadad, et al 2011;Mangabeira et al 2011). Low concentration of the metal in the aerial parts of E. crassipes may be due to the slow mobility of metal after being taken up by roots.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…crassipes accumulated higher Cr concentrations in roots than in the aerial parts of the plant (Figs. 1 and 2), in agreement with many authors (Ingole and Bhole 2003;Maine, et al 2004;Paiva et al 2009;Hadad, et al 2011;Mangabeira et al 2011). Low concentration of the metal in the aerial parts of E. crassipes may be due to the slow mobility of metal after being taken up by roots.…”
Section: Discussionsupporting
confidence: 89%
“…Chromium is not considered an essential element for plant nutrition (Shanker et al 2004;Mangabeira et al 2011). However, Cr (III) and Cr (VI) can be taken up by plants using different uptake mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to high Cr-concentration causes mitochondrial damages, such as outer membrane rupture, swelling, deformed or altered internal cristae, dense electron accumulated materials, and spherical morphology [23,118,119]. It has been also reported that mitochondria were underdeveloped in the Brassica napus seedlings that were exposed to 400 µM Cr as compared seedlings exposed to control conditions [41,120].…”
Section: Cr-induced Necrosis and Cellular Injurymentioning
confidence: 97%
“…For instance, Cr concentration was observed to be highest in the cytoplasm and intercellular spaces of rhizome and root cell wall of Iris pseudacorus [54]. The higher accumulation of Cr in roots might be attributed to the sequestration of Cr in the vacuoles of root cells as a protective mechanism [55]. Thus, this mechanism provides some natural tolerance to plants towards Cr toxicity [40].…”
Section: Chromium Uptake Translocation and Sub-cellular Distributionmentioning
confidence: 99%